2016
DOI: 10.1590/1807-1929/agriambi.v20n7p672-677
|View full text |Cite
|
Sign up to set email alerts
|

Drying kinetics of atemoya pulp

Abstract: A B S T R A C TThis study was conducted in order to obtain drying curves of whole atemoya pulp through the foam-mat drying method. The suspension was prepared with whole atemoya pulp mixed with 2% of Emustab ® and 2% of Super Liga Neutra ® with mixing time of 20 min, and dried in a forced-air oven at different temperatures (60; 70 and 80 °C) and thicknesses of the foam layer (0.5, 1.0 and 1.5 cm). The drying rate curves were plotted against the water content ratio and the semi-theoretical models of Henderson &… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
3
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 14 publications
7
3
0
4
Order By: Relevance
“…Water losses are higher in the beginning of the drying process, after which the losses decrease with consequent reduction in the drying rate. A similar behavior was observed by Galdino et al (2016) in the foam-mat drying of atemoya pulp at different temperatures (60, 70 and 80 °C) and thicknesses (0.5, 1.0 and 1.5 cm). There is a trend of increase in the effective diffusivity with the increment of pulp layer thickness and with the increment in temperature.…”
Section: A Bsupporting
confidence: 83%
“…Water losses are higher in the beginning of the drying process, after which the losses decrease with consequent reduction in the drying rate. A similar behavior was observed by Galdino et al (2016) in the foam-mat drying of atemoya pulp at different temperatures (60, 70 and 80 °C) and thicknesses (0.5, 1.0 and 1.5 cm). There is a trend of increase in the effective diffusivity with the increment of pulp layer thickness and with the increment in temperature.…”
Section: A Bsupporting
confidence: 83%
“…The value of moisture content ratio decreased abruptly as drying temperature increased (Figure 1). In addition, as drying air temperature increased, a higher product water removal rate was observed, as reported in several studies for different plant products (Ferreira et al, 2012;Santos et al, 2013;Baptestini et al, 2016;Galdino et al, 2016). Table 2 shows the values of the chi-square test and estimated mean error (SE) obtained for the different models fitted to the drying curves of baru fruits.…”
Section: Resultssupporting
confidence: 55%
“…This shows the high affinity of the model to the experimental data, being able to be used in the prediction of the drying process in the palm shoot with high degree of confidence within the temperature range worked in this study. Galdino et al (2016) studying the drying kinetics of atemoia pulp, observed a behavior similar to that of the present study with higher values of R 2 above 0.9, for the Page, Midilli and Henderson & Pabis models in temperature ranges 60, 70 and 80 °C.…”
Section: Resultssupporting
confidence: 88%